A arborização de acompanhamento viário e a verticalização na Zona 7 de Maringá-PR - Tudini, Odilon Groxiatti (2006)
The changes that frequently occur in the urban space due the accelerated urbanization are directly related with many environment processes and conflicts. The actual man doesn't see the green areas like an important aspect to natural balance in the landscape. This same man sees the progress in big buildings like high edifices. These types of constructions bring prestige and formality to the cities. The major objective from this work was analyzed a zone present intense dynamic in the urban space, the Zone 7 from Maringá-PR. The interactions between street arborization and verticalization process were studied. It was used a methodology based on technique, empiric and theoretic-methodological analysis. The analysis from dates obtained from research in field showed that Zone 7 present 6032 trees and about 57,82% were classified in suffering category, indicating that these trees required special carries. Only two species of tree, the Caesalpinia peltophoroides (Sibipiruna) and the Tipuana tipu (Tipuana), compose 64,19% from total arborization present in this zone. The low species diversity may lead to great losses of trees due to the incidence of specific pestes (for example, termites) or diseases. In order to analyzed the relationship between arborization and verticalization (conflicts) the zone was divided in 9 areas according to number of edifices, local characteristics and type of verticalization process that occurred in each area. The different areas were denominated as following: i) areas presenting vertical concentration (AV-1, divided in AV-1A, AV-1B and AV-1C; e AV-2, divided in AV-2A and AV-2B); ii) areas presenting verticalization (PV-1 and PV-2); iii) areas presenting verticalization on initial phase (PVI-1 and PVI-2). Different conflicts were observed in arborization/verticalization relation. These conflicts could be classified as direct conflicts caused by physical confront between trees and edifices (i.e. trim trees and trees surrounded by areas presenting impenetrable ground cover that blocked nutrients acquisition) or indirect conflicts due diverse processes caused by edifices in urban space (i.e. areas presenting excessive shadow, air corridor and humidity). In other words the arborization present in Zone 7 is influenced by verticalization process. These negative impacts could be reduced if the public power to take necessary steps such as provided the foundation the management plan and supervisions of abuses related with trees present in this zone and in Maringá city.